Profiling Mycobacterium ulcerans: sporulation, survival strategy and response to environmental factors - Eunice Ampadubea Ayerakwa; Molly Kukua Abban; Abiola Isawumi; Lydia Mosi (Future Science OA)
Mycobacterium ulcerans is the causative agent of Buruli ulcer – a necrotizing skin infection. As an environmental pathogen, it has developed stress response mechanisms for survival. Similar to endospore formation in M. marinum, it is likely that M. ulcerans employs sporulation mechanisms for its survival and transmission. In this review, we modeled possible transmission routes and patterns of M. ulcerans from the environment to its host. We provided insights into the evolution of M. ulcerans and its genomic profiles. We discuss reservoirs of M. ulcerans as an environmental pathogen and its environmental survival. We comprehensively discuss sporulation as a possible stress response mechanism and modelled endospore formation in M. ulcerans. At last, we highlighted sporulation associated markers, which upon expression trigger endospore formation.